(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
As a crucial part of service business management, quality control is essential for making sure that a business’s offerings consistently satisfy its clientele. Since Nigeria’s service industry has expanded rapidly in recent years, quality assurance is more vital than ever. The purpose of this research is to determine the effect of quality control performance of service business in Nigeria. Research data from Nigerian service providers was gathered using a qualitative methodology that included in-depth interviews and case studies. According to the results, quality control has a beneficial effect on the productivity of Nigerian service providers by raising levels of client satisfaction, staff dedication, and operational efficacy. On the other hand, the research showed that many Nigerian service providers fail to adopt quality control systems owing to an inadequacy of expertise and funding. Conclusions from the research stress the importance of quality control in the management of Nigerian service organizations and the need for further efforts to train and assist the sector’s practitioners.